Assessment of Hydrochemical Facies on Groundwater Quality in Daenaa Village and its Surroundings, West Limboto District - Dela Pusfika Sari Napu; Fitryane Lihawa; Ahmad Zainuri (Jambura Geoscience Review, 2023)
The study is required to evaluate the groundwater condition, such as finding the relationship with the lithology, determining the facies of groundwater, and providing an overview of the present groundwater conditions, genetics, and groundwater quality. This study aims to explain the relationship between lithology and groundwater chemistry, groundwater quality, and the determination of the chemical facies of groundwater to determine the genetic type of groundwater. This study uses field survey methods and random sampling techniques, measurements of groundwater physical properties, trilinear piper diagrams, and laboratory analysis in the form of rock geochemical analysis (XRF) at the PSDMBP Laboratory and chemical analysis of groundwater at the PT Global Quality Analytical Laboratory. The results show that the lithology in the study area consists of clastic limestone, sandstone, breccia, and dacite. Lithology in the study area primarily plays an essential role in chemical ion enrichment in groundwater. Determination of groundwater quality is based on Permenkes, Permen ESDM, and ISDW, which obtained eleven well points in the good quality category, five well points in the poor quality category, and four other well points categorized as poor quality. Based on the analysis results in the trilinear piper diagram, there is one type of groundwater chemical facies (not varied), namely the Ca-Cl type facies. The presence of the Ca-Cl facies type is interpreted as a seawater intrusion phase.